Sophia princess among beasts [large type] - Patterson, James, 1947-; Raymond, Emily, 1972- (Little, Brown and Company, 2019)
In a kingdom besieged by hunger, sickness, and war, Princess Sophia must do whatever it takes to protect the people she loves, even if it means she has to confront the beasts she thought only lived in her books.